Malaria and agriculture: A global review of the literature with a focus on the application of integrated pest and vector management in East Africa and Uganda - Wielgosz, Benjamin; Mangheni, Margaret Najjingo; Tsegai, Daniel; Ringler, Claudia (International Food Policy Research Institute, 2012)
Malaria is one of the top five causes of death worldwide, and roughly half the world’s population lives at risk of the disease. This health problem disproportionately affects the poor, particularly those in Africa south of the Sahara, where the disease is widespread. Many of those most afflicted are part of farming households; therefore agriculture, poverty, and health are intimately linked through malaria. Uganda has the highest malaria parasite transmission in the world and is an important case study due to the role agricultural development has played in increasing malaria transmission within the country, according to the literature reviewed here. This review brings together current research from agricultural economics, environmental science, and epidemiology to provide a foundation for research directly addressing how malaria relates these fields to one another in malaria-endemic settings such as the East African highlands. While each field has addressed malaria within existing academic frameworks, this literature review should support further interdisciplinary research by providing a detailed and well-documented account of integrative work on malaria to date.